2008
DOI: 10.1002/lite.200800065
|View full text |Cite
|
Sign up to set email alerts
|

The oxidative stability of biodiesel: Effects of FAME composition and antioxidant

Abstract: A significant problem associated with the commercial acceptance of biodiesel is poor oxidative stability. This study investigated the effectiveness of individual and binary antioxidants to improve the oxidative stability of different types of biodiesel and distilled biodiesel. Results indicate that different types of biodiesel have different levels of oxidative stability, and that natural antioxidants and FAME composition play significant roles in determining oxidative stability. Synthetic antioxidants can enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(23 citation statements)
references
References 4 publications
3
20
0
Order By: Relevance
“…To increase the oxidation stability of COME, it was doped with stabilizers or antioxidants. These were selected on the basis of their chemical structure, quality, cost, availability as well as previous studies on biodiesel and vegetable oils used in the food industry [21][22][23]. The antioxidants chosen for this study were 1,2,3 tri-hydroxy benzene (Pyrogallol, PY), 3,4,5-tri hydroxy benzoic acid (Propyl Gallate, PG) and 2-tert butyl-4-methoxy phenol (Butylated Hydroxyanisole, BHA).…”
Section: Oxidation Stability Of Croton Oil Methyl Estermentioning
confidence: 99%
“…To increase the oxidation stability of COME, it was doped with stabilizers or antioxidants. These were selected on the basis of their chemical structure, quality, cost, availability as well as previous studies on biodiesel and vegetable oils used in the food industry [21][22][23]. The antioxidants chosen for this study were 1,2,3 tri-hydroxy benzene (Pyrogallol, PY), 3,4,5-tri hydroxy benzoic acid (Propyl Gallate, PG) and 2-tert butyl-4-methoxy phenol (Butylated Hydroxyanisole, BHA).…”
Section: Oxidation Stability Of Croton Oil Methyl Estermentioning
confidence: 99%
“…The biodieseloxidation stability has been found in this study to be lower than the standard. 24, 25 Tang et al 6 found that antioxidants improved the oxidation stability of biodiesel, suggesting that antioxidants could be added to the FAMEs in the present study to improve the oxidation stability. Moser 7 determined that methyl esters that contained 10 or less carbons in the fatty acid backbone were unacceptable for stability analysis at 110°C (EN 14112) due to excessive sample evaporation, but the FAME used in this study had more than 10 carbons that allowed for proper oxidation stability determination.…”
Section: Introductionmentioning
confidence: 87%
“…According to the prediction of reaction rate kinetics, the biodiesel blend can be stored more 449 days. However, approximately 200 ppm and 150 ppm of PDA was required to guarantee a half year of storage, which is the current recommendation for biodiesel shelf life [24,25], based on EN 14,112 and EN 15,751, respectively. It was obvious that the further study is required to verify the validity of the two prediction models for biodiesel shelf life.…”
Section: Ip At Ambient Temperature As Obtained By An Extrapolation Mementioning
confidence: 99%